Step
*
1
of Lemma
quadratic2-zero
1. a : ℝ
2. b : ℝ
3. c : ℝ
4. a ≠ r0
5. c = r0
6. b ≤ r0
7. r0 ≤ ((b * b) - r(4) * a * c)
8. ((b * b) - r(4) * a * c) = (b * b)
9. r(2) * a ≠ r0
⊢ (-(b) - |b|/r(2) * a) = r0
BY
{ ((RWO  "rabs-of-nonpos" 0 THENA Auto) THEN nRNorm 0 THEN Auto) }
Latex:
Latex:
1.  a  :  \mBbbR{}
2.  b  :  \mBbbR{}
3.  c  :  \mBbbR{}
4.  a  \mneq{}  r0
5.  c  =  r0
6.  b  \mleq{}  r0
7.  r0  \mleq{}  ((b  *  b)  -  r(4)  *  a  *  c)
8.  ((b  *  b)  -  r(4)  *  a  *  c)  =  (b  *  b)
9.  r(2)  *  a  \mneq{}  r0
\mvdash{}  (-(b)  -  |b|/r(2)  *  a)  =  r0
By
Latex:
((RWO    "rabs-of-nonpos"  0  THENA  Auto)  THEN  nRNorm  0  THEN  Auto)
Home
Index